2014
DOI: 10.15255/kui.2013.027
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Total Flavonoids Extraction from Coreopsis tinctoria Nutt. by Response Surface Methodology

Abstract: Response surface methodology (RSM) was applied to predict optimum conditions for extraction of flavonoid from Coreopsis tinctoria Nutt. A central composite design (CCD) was used to monitor the effect of extraction temperature, extraction time, and water-to-material ratio on yield of total flavonoids. The optimal extraction conditions were obtained as water-to-material ratio of 55 ml g −1 , extraction temperature of 80 °C and extraction time of 70 minutes. Under these conditions, the average total flavonoids yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…[110] CODEN (USA): AJPRHS diffusion rate during extraction, high temperature also causes degradation of phenolic compounds 22 . In addition, flavonoids are also heat-sensitive and high extraction temperature lead to compound degradation 23 . HPLC profiling of both extracts as well as compound identification were conducted and chromatograms are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…[110] CODEN (USA): AJPRHS diffusion rate during extraction, high temperature also causes degradation of phenolic compounds 22 . In addition, flavonoids are also heat-sensitive and high extraction temperature lead to compound degradation 23 . HPLC profiling of both extracts as well as compound identification were conducted and chromatograms are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…In a study carried out by Liu et al [33], with a fixed water-to-raw-material ra- shown that the application of very high temperatures (≥95˚C) may also alter the concentration and composition of phenolic compounds [38]. Although some researchers hold the view that the critical temperature for flavonoid extraction is below 80˚C [39], this threshold temperature would be variable in different plants and plant organs, with PAL or CHS enzymes activity mediating the effects [40].…”
Section: Resultsmentioning
confidence: 99%
“…Beyond an optimum range, the increase in the concentration of plasticizer led to remarkable results in the mechanical strength of the composites (Liu et al 2014). The use of a plasticizer resulted in the conformational changes, via altered interactions between the host polymers to the reinforcement fibre (Kfoury et al 2013), and thus contributed to increased mobility.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 99%